Mutual authentication quantum key agreement protocol with single-particle measurement - Yang, Hao; Yi, Zepu; Lu, Songfeng; Wang, Mu (Frontiers in Physics, 2025)
In this paper, a mutual authentication quantum key agreement protocol with single-particle measurement is proposed. The participants can authenticate each other’s identity through their secret identity information and the entanglement property of Bell states. After the authentication phase, the participants can negotiate a private key with equal contribution. We prove that the proposed scheme is unconditional security. In comparison to the previous mutual authentication quantum key agreement protocols, the proposed method utilizes Bell states as the quantum resource states in both the identity authentication and key agreement stages. It requires single-particle measurement without the need for Bell measurements or the involvement of trusted or semi-trusted other participants. Additionally, our proposed scheme demonstrates significant advantages in terms of qubit efficiency.